Rapid Differential Detection of Japanese Encephalitis Virus and Getah Virus in Pigs or Mosquitos by a Duplex TaqMan Real-Time RT-PCR Assay - Zhang, Yan; Li, Yuhao; Guan, Zhixin; Yang, Yang; Zhang, Junjie; Sun, Qing; Li, Beibei; Qiu, Yafeng; Liu, Ke; Shao, Donghua; Ma, Zhiyong; Wei, Jianchao; et al. (Frontiers in Veterinary Science, 2022)
Both JEV (Japanese encephalitis virus) and GETV (Getah virus) pose huge threats to the safety of animals and public health. Pigs and mosquitoes play a primary role in JEV and GETV transmission. However, there is no way to quickly distinguish between JEV and GETV. In this study, we established a dual RT-qPCR method based on double TaqMan probes for rapid identification and detection of JEV and GETV. Primers and probes located in the NS1 gene of JEV and the E2 gene of GETV that could specifically distinguish JEV from GETV were selected for duplex TaqMan RT-qPCR. In duplex real-time RT-qPCR detection, the correlation coefficients (R2) of the two viruses were higher than 0.999. The RT-qPCR assay demonstrated high sensitivity, extreme specificity, and excellent repeatability. Detection of JEV and GETV in field mosquito and pig samples was 100 times and 10 times more sensitive than using traditional PCR, respectively. In addition, the new test took less time and could be completed in under an hour. Clinical sample testing revealed the prevalence of JEV and GETV in mosquitoes and pig herds in China. This complete duplex TaqMan RT-qPCR assay provided a fast, efficient, specific, and sensitive tool for the detection and differentiation of JEV and GETV.